2018
DOI: 10.1111/jfd.12912
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative investigation of Enteromyxum leei (Myxozoa: Myxosporea) infection and relative condition factor in cultured olive flounder Paralichthys olivaceus (Temminck and Schlegel)

Abstract: Enteromyxum leei has been reported to cause emaciation disease in various fish species. To determine the effect of parasite intensity on cultured olive flounder Paralichthys olivaceus, we investigated the relationship between the relative condition factor (rCF = CF/standard CF × 100) and parasite load with quantitative polymerase chain reaction (qPCR) and the challenge test. A total of 57 cultured olive flounders were obtained from 11 fish farms and divided into five groups based on their rCF. We investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
(63 reference statements)
1
2
0
Order By: Relevance
“…Altered permeability may lead to impaired digestive functions and reduced fish growth [75], and arrested growth is one of the disease signs of this enteritis [76, 77]. In the present study, this was also evidenced by the differences in weight between R and C fish at the end of all trials.…”
Section: Discussionsupporting
confidence: 59%
“…Altered permeability may lead to impaired digestive functions and reduced fish growth [75], and arrested growth is one of the disease signs of this enteritis [76, 77]. In the present study, this was also evidenced by the differences in weight between R and C fish at the end of all trials.…”
Section: Discussionsupporting
confidence: 59%
“…Both Farms A and B had a decrease in rCF from September to November. In our previous study, olive flounder infected by E. leei showed that rCF decreased by approximately 10% over 9 w (Shin et al., 2018b). An experimental infection of E. leei in tiger puffer, Takifugu rubripes (Temminck & Schlegel), showed high mortality, with emaciation occurring 42 to 63 days after infection (Yanagida et al., 2006).…”
Section: Figurementioning
confidence: 87%
“…The pellets were used in the genomic DNA extraction, using the QIAamp DNA Mini Kit (Qiagen), as per the manufacturer's protocol. The E. leei 28S ribosomal DNA (rDNA) copy number in each sample was determined using the method described previously (Shin et al., 2018b). Briefly, partial 28S rDNA of E. leei was amplified by PCR and purified.…”
Section: Figurementioning
confidence: 99%